The Role of Gut Bacteria and Plasma Metabolites in Predicting Post-Stroke Depression in Patients with Acute Ischemic Stroke - Wen, Lulu; Si, Tong; Yan, Chuming; Shen, Huixin; Zheng, Wancheng; Xiu, Meihong; Qu, Miao (Current Neuropharmacology, 2025)
<span class=
Keywords: biomarkers